In vitro Antimicrobial Activity Test of Zingiber officinale var. rubrum Rhizome Extract against Methicillin-Sensitive Staphylococcus aureus (MSSA) and Methicillin-Resistant Staphylococcus aureus (MRSA) - Jieputra, Alden; Purwanta, Marijam; Mustika, Arifa; Retnowati, Wiwin (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: Staphylococcus aureus, particularly MRSA, had developed rapid resistance against antibiotics like beta-lactams. Red ginger is believed to be antibacterial against MSSA and MRSA in vitro. Red ginger rhizome extracts displayed weak activity against MSSA and MRSA.   Abstract Introduction: Red ginger (Zingiber officinale var. rubrum) is a traditional herb that is believed to possess antibacterial properties. Throughout the years, Staphylococcus aureus has developed resistance to a broad range of antibiotics, including beta-lactams, particularly in the form of Methicillin-Resistant Staphylococcus aureus (MRSA). As treatment options dwindle, it is urgent to formulate novel antibiotics. This study aimed to examine the antibacterial activity of the ginger rhizome ethanol extract against Methicillin-Sensitive Staphylococcus aureus (MSSA) and MRSA. Methods: This study was performed according to the post-test-only control group design. Through a good diffusion assay, the anti-MSSA and anti-MRSA activity of the red ginger extract concentrations (100%, 50%, 25%, 12.5%, and 6.25%) was observed by measuring the diameter of the clear inhibition zones. Dimethyl sulfoxide (DMSO) and an antibiotic disc were added as control groups. Results: The red ginger extracts produced inhibition zones on both MSSA and MRSA. However, the antibacterial activity was considered weak (<12 mm). The concentration of the extract appeared to linearly affect its antibacterial activity against MSSA and MRSA. On MSSA, the 12.5% extract results differed significantly from those of the 100% and 50% extracts. Meanwhile, on MRSA, the extracts seemed to yield significantly different outcomes when compared to each other, except for the comparisons between 50%-25% and 12.5%-6.25%. Conclusion:Zingiber officinale var. rubrum rhizome extracts showed weak antibacterial activity against MSSA and MRSA.